The Saskatchewan Trade Union Act. 1983: The Public Battle - Sass, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This article reviews Labour's response to the Amendments, and concludes that the new amendments to The Trade Union Act indicate that the Government of the day leans more towards management's objectives than those of trade unions with regard to collective bargaining.